Terapi Mendongeng untuk Perkembangan Bahasa Pada Anak Adzif Dengan Speech Delay di RA Fun Islamic School Purworejo - ., Nurjanah; Muyasiroh, Rif’atus Sa’idatul; Haq, Muhammad Zaairul (STAINU Purworejo, 2018)
This study discusses language development in Nadzif children with speech delay in KB / RA FIS (Fun Islamic School) with storytelling method. This study uses a qualitative method of case study with early childhood research in KB / RA FIS (Fun Islamic School) Teaching Group 2018/2019 which is examined as many as 1 child as the subject of the study is Nadif children who are criterias experiencing speech delay Collection data is done using the method of observation, interviews, and documentation. The results showed that the influence of storytelling activities was able to increase vocabulary, children able to speak and language of children increased this can be seen until now Nadzif children are able to improve communication with their peers, with mothers in school and there are many changes in language development when communicating with parents at home